Job Satisfaction and Employee Performance in Indonesia - Angga Kurniawan (SAJMR : Southeast Asian Journal of Management and Research, 2023)
This study aims to determine the extent to which motivation, and communication on job satisfaction and their impact on the performance of employees of construction service companies in Indonesia. The data used in this study are primary data collected from respondents' answers based on the questionnaire given, as many as 305 people. The analysis method uses the Path Analysis method with the help of SPSS version 22.0. Statistical testing uses the simultaneous significance test (F test), the individual parameter significance test (t test) and the Sobel test mediation test. The results showed that simultaneously the variables of motivation, communication and job satisfaction had a direct influence on employee performance. Partially shows that the motivation variable and the communication variable have a positive correlation and have a direct and indirect effect on employee performance. While the implications of the variable job satisfaction as an intervening variable have a direct influence on employee performance. The results showed that job satisfaction had a direct positive and significant effect on employee performance. Based on the results of the analysis, the path coefficient (Beta) of the job satisfaction variable on the employee performance variable is 0.645 with a significance of 0.001.